Luteolin exerted less inhibitory effect on macrophage activation induced by Astragalus polysaccharide than by lipopolysaccharide. (October 2017) - Li, Zhi-Peng; Zhang, Quan-Wei; Wei, Wei; Li, Li-Feng; Ma, Dik-Lung; Leung, Chung-Hang; Lu, Ai-Ping; Bian, Zhao-Xiang; Han, Quan-Bin
Highlights: Luteolin reduced NO level and iNOS gene level in RAP or LPS induced RAW264.7 cells. Luteolin reduced cytokines level in LPS induced RAW264.7 cells. Luteolin did not reduce cytokines level obviously in RAP induced RAW264.7 cells. Luteolin inhibited NF-κB p65 and Akt activation in RAP induced RAW264.7 cells. Luteolin did not inhibit MAPKs and IRF3 activation in RAP induced RAW264.7 cells. Abstract: As a kind of food supplementary, polysaccharide-rich tonic herbs become more and more popular. However, little is known regarding the interaction between known active molecules with these polysaccharides. This study aims to investigate effects of luteolin on RAW264.7 cells induced by Astragalus polysaccharide RAP in comparison with lipopolysaccharide (LPS). The results showed that luteolin suppressed inflammatory meditors in LPS-induced RAW264.7 cells. While in the RAP-induced RAW264.7 cells, luteolin only decreased the NO production and iNOS gene expression, but only inhibit IL-6 at high concentration, and was ineffective in term of TNF-α. The results of western blot analysis suggested that luteolin only inhibited the phosphorylation of NF-κB p65 and Akt, but not MAPKs and IRF3 in RAP-induced RAW264.7 cells. Taken together, lutelion exerted less inhibitory effect on macrophage induced by RAP than by LPS. This study demonstrated the luteolin-containing foods may not strongly interfere the immunoregulation effect of polysaccharide RAP.